Strategies to improve manual operation of irrigation systems in Sri Lanka - Godaliyadda, G.G.A. (Irrigation Dept., Colombo (Sri Lanka).); Renault, D; Hemakumara, H.M; Makin, I.W (Irrigation and drainage systems, 1999)
Improvements to normal operational procedures are investigated for the main types of irrigation system identified in Sri Lanka. Scheduled and unscheduled changes of flow regime the systems are likely to experience and the opportunities for improved operations related to the physical characteristics of each type are analyzed. Performance of several alternative manual operational procedures are evaluated and compared using a hydraulic model (Simulation of Irrigation Canal, SIC) for three different irrigation subsystem types (Single Bank canal; Double Bank canal; Canals with intermediate Storage). Results of these simulations show that current practice, based on a fixed frequency of operation of 12 hrs and a target water depth set to the spill level of the cross-regulator, is not far from the optimal for systems without on-line storage. A slight improvement can be expected if the frequency of operation is increased to 6 hrs. For systems with on-line storage it is recommended to split operational procedures into two parts, one related to the canal and one to the storage. Among different options investigated, discharge control at the downstream regulator of the storage appears to be the most reliable as it performs well whatever operation procedures are selected for the canal. Irrigation systems in Sri Lanka are subject to frequent positive flow changes (Supply fluctuations, Runoff, Return-flow changes). As far as water management is concerned, improvements to be expected from normal operation procedures appear to be somewhat limited because management of flow changes is not an objective. For instance little effort is made to harvest runoff under the current practices. One conclusion of the study is that new strategies for the harvest, storage and release of positive flow changes should be tested and, where appropriate, implemented to improve the overall efficiency of operation in irrigation systems in Sri Lanka.